1998
DOI: 10.1161/01.atv.18.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reducing Dietary Saturated Fatty Acids on Plasma Lipids and Lipoproteins in Healthy Subjects

Abstract: Few well-controlled diet studies have investigated the effects of reducing dietary saturated fatty acid (SFA) intake in premenopausal and postmenopausal women or in blacks. We conducted a multicenter, randomized, crossover-design trial of the effects of reducing dietary SFA on plasma lipids and lipoproteins in 103 healthy adults 22 to 67 years old. There were 46 men and 57 women, of whom 26 were black, 18 were postmenopausal women, and 16 were men > or =40 years old. All meals and snacks, except Saturday dinne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
1
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(166 citation statements)
references
References 75 publications
13
143
1
8
Order By: Relevance
“…MUFA has, however, been associated with higher HDL cholesterol concentrations, 15,30 reflected in lower total:HDL cholesterol and LDL-:HDL cholesterol ratios, as potentially important predictors of cardiovascular risk. 21 Higher SFA intakes in exchange for carbohydrate in the DELTA (Dietary Effects on Lipoproteins and Thrombogenic Activity) study were associated with a lower Lp(a) level, 31 an effect associated in the present study with higher MUFA intakes. This lipid risk factor for CHD is not altered by most dietary and pharmacological treatments, and the effect of almonds is therefore notable.…”
Section: Discussionsupporting
confidence: 48%
“…MUFA has, however, been associated with higher HDL cholesterol concentrations, 15,30 reflected in lower total:HDL cholesterol and LDL-:HDL cholesterol ratios, as potentially important predictors of cardiovascular risk. 21 Higher SFA intakes in exchange for carbohydrate in the DELTA (Dietary Effects on Lipoproteins and Thrombogenic Activity) study were associated with a lower Lp(a) level, 31 an effect associated in the present study with higher MUFA intakes. This lipid risk factor for CHD is not altered by most dietary and pharmacological treatments, and the effect of almonds is therefore notable.…”
Section: Discussionsupporting
confidence: 48%
“…In well-controlled studies with a large number of subjects (Ginsberg et al, 1998;Howard et al, 1995;Mensink & Katan, 1990), they showed that diet effects were similar in women and men when they investigated the effects of reducing the dietary saturated fatty acids on serum total and LDL cholesterol concentrations. In this study, the ratio of polyunsaturated to saturated fat was 3.0 in the walnut diet and 1.0 in the reference diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, most were short term, and only a few presented sex-specific results. The diet studies that have provided sex-specific data disagree, reporting similar HDL-C responses between women and men, 10,28,32,35 greater reductions in women, 7,8,31 and greater reductions in men. 38 The discrepancies in these reported results may reflect the differences in study protocols, including subject characteristics, provided versus selfselected foods, nutrient composition, and usually short study duration.…”
Section: Walden Et Al Hdl Andmentioning
confidence: 98%